In vitro shoot regeneration through anther culture of Brassica spp. (Bangladesh Journal of Agricultural Research, 2010)
The experiment was conducted to investigate the performance of three different genotypes (BARI Sarisha-6, BARI Sarisha-8, and BARI Sarisha-11) in two different media viz., MS and B5 with different concentrations of phytohormone (2, 4-D) for callus induction from uninucleate stage anthers of Brassica and subsequent plant regeneration in MS media with different concentrations of phytohormone (BAP and NAA). Among the genotypes, BARI Sarisha-8 showed the best performance for all the parameters of callus induction. The performance of BARI Sarisha-6 was poor compared to others. Maximum rate of callus induction (%) was observed in MS + 0.5 mg/L 2, 4-D followed by B5 + 0.5 mg/L 2,4-D. The media combination MS + 1.0 mg/L BAP 0.3 mg/L 2,4-D showed the best performance for maintenance of calli. Significant variations were observed among the genotypes and media composition for shoot regeneration. Among the genotypes, BARI Sarisha-8 showed the best performance for shoot regeneration followed by BARJ Sarisha-l1. The genotype BARI Sarisha-8 produced higher percent of shoots/calli and required minimum days for shoot initiation. Higher percent calli without shoot were produced by the genotype BARI Sarisha-6. The media combination MS + 2.0 mg/L BAP + 0.5 mg/L NAA showed the best performance for shoot regeneration and required maximum days for shoot initiation. Keywords: Regeneration; BARI Sarisha-6; BARI Sarisha-8; BARI Sarisha-11; anther culture; phytohormone  DOI: 10.3329/bjar.v35i2.5896Bangladesh J. Agril. Res. 35(2) : 331-341, June 2010